Radiation Safety and External Radiation Exposure Rate of Patients Receiving I-131 Therapy for Hyperthyroidism and Remnant Ablation as Outpatient: An Institutional Experience - Bhatia, Nisha; Dhingra, Vandana K.; Mittal, Pulkit; Saini, Sunil (World Journal of Nuclear Medicine, 2023)
Objective Our objective was to study the radiation exposure rate as function of time in the administration of radioiodine iodine-131 (I-131) for the treatment of thyrotoxicosis or Graves' disease and remnant ablation on an outpatient basis at the Department of Nuclear Medicine, and also, to study the impact of revised discharge criteria for radioiodine therapy enforced by the Atomic Energy Regulatory Board (AERB) of India.Materials and Methods This study included patients who underwent low-dose radioiodine therapy using I-131. Patients were classified into two different groups, that is, group A and group B. Group A included patients receiving low dose I-131 for the treatment of thyrotoxicosis, whereas group B included patients receiving I-131 therapy for the ablation of residual thyroid tissue after total thyroidectomy. The radiation exposure rate was measured using a radiation detector in milli roentgen per hour (mR/h) at 5 cm distance of stomach and neck levels and with the patient standing at the distance of 1 m after oral administration of I-131 at 0, 1, and 2 hours.Results A total of 134 (17 males and 117 females) patients were included in the study. Group A comprised 102 (14 male and 88 females) patients and group B of 32 (3 males and 29 females) patients. At the neck level, the average exposure rate in group A versus group B after 0, 1, and 2 hours was observed to be 6.9 versus 22.27 mR/h, 33.67 versus 43.39 mR/h, and 41.75 versus 48.90 mR/h, respectively. At the stomach level, the exposure rate was 23.65 versus 71.32 mR/h, 13.27 versus 48.45 mR/h, and 9.91 versus 39.43 mR/h after 0, 1, and 2 hours, respectively. At a distance of 1 m, the exposure rate was 1.31 versus 2.99 mR/h, 1.05 versus 2.58 mR/h, and 0.92 versus 2.21 mR/h, respectively.Conclusion Exposure rate measured for patients treated with up to 1,110 MBq (30 mCi) of I-131 was under permissible limits as per revised discharged limits, that is, 50 µSv/h (5 mR/h) prescribed by AERB, India. The patients undergoing radioiodine therapy I-131 (up to 1,110 MBq/30 mCi) can be discharged safely 2 hours postadministration following good work practice along with providing proper radiation safety instructions to patients.
Keywords: radioiodine therapy; thyrotoxicosis; ablation; outpatient; radiation exposure